2022
DOI: 10.1080/13880209.2022.2106250
|View full text |Cite
|
Sign up to set email alerts
|

Integrated strategy of RNA-sequencing and network pharmacology for exploring the protective mechanism of Shen-Shi-Jiang-Zhuo formula in rat with non-alcoholic fatty liver disease

Abstract: Context Shen-Shi-Jiang-Zhuo formula (SSJZF) exhibits a definite curative effect in the clinical treatment of non-alcoholic fatty liver disease (NAFLD). Objective To explore the therapeutic effect and mechanism of SSJZF on NAFLD. Materials and methods Sprague Dawley rats were randomly divided into control, NAFLD, positive drug (12 mg/kg/day), SSJZF high-dose (200 mg/kg/day), SSJZF middle-dose (100 mg/kg/day), and SSJZF low-dose (50 mg/kg/day) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…We performed a detailed computational investigation into the impact of the E 471 V and G 798 D mutations for the structure of the S protein using molecular modelling and molecular mechanics/generalized borne surface area (MM/GBSA) free energy calculations. The open conformation structure of S protein trimer from the glycosylated BA.2 Omicron variant was used for residue variant mapping [PDB 7XO8; (14)]. Because the crystal structure shows the trimer bound to the human ACE2 (hACE2) receptor, it is possible to investigate the impact of mutations in the hACE2 RBD and predict favorable interactions between SARS-CoV-2 S protein and hACE2 as previously reported (15) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a detailed computational investigation into the impact of the E 471 V and G 798 D mutations for the structure of the S protein using molecular modelling and molecular mechanics/generalized borne surface area (MM/GBSA) free energy calculations. The open conformation structure of S protein trimer from the glycosylated BA.2 Omicron variant was used for residue variant mapping [PDB 7XO8; (14)]. Because the crystal structure shows the trimer bound to the human ACE2 (hACE2) receptor, it is possible to investigate the impact of mutations in the hACE2 RBD and predict favorable interactions between SARS-CoV-2 S protein and hACE2 as previously reported (15) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our focus was on examining the local impact of E 471 V and G 798 D on the favorability of S protein-hACE2 interaction and the modifications in the S2 site as a hypothesis for the experimentally observed traits found in SARS-CoV-2 wildlife reservoir. Here, the open conformation structure of the S protein trimer from the glycosylated BA.2 Omicron variant was used for residue variant mapping [PDB 7XO8] 23 . Because the crystal structure shows the trimer bound to the human ACE2 (hACE2) receptor, it is possible to investigate the local impact of mutations in the RBD on interactions between SARS-CoV-2 S protein and the human ACE2, as a prediction for mechanistic impact on S protein-ACE2 interaction favorability as previously reported and validated experimentally 24 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Wu, et al (2023b) found through network pharmacological study that The liver protective effect of QTHX is closely related to oxidative stress, anti-inflammatory response, and lipid receptor signaling, and QTHX has been shown to treat liver inflammation in rats by activating the SCOS1/NF-κB/TLR4 pathway. Xu, et al (2022) conducted a comprehensive analysis of Shen-Shi-Jiang-Zhuo formula (SSJZF) by RNA sequencing and network pharmacology, and found 23 main compounds of SSJZF and 25 key therapeutic targets for NAFLD. SSJZF was proven to improve NAFLD in rats by activating the PI3K/Akt pathway.…”
Section: Network Pharmacological Study On Non-alcoholic Fatty Liver D...mentioning
confidence: 99%